Bacterial isolates and their antibiotic susceptibility patterns among patients with pus and/or wound discharge at Gondar university hospital - Dagnachew Muluye; Yitayih Wondimeneh; Getachew Ferede; Tesfaye Nega; Kasaw Adane; Belete Biadgo; Habtie Tesfa; Feleke Moges (2014)
In spite of advances in control of infections, wound infections have not completely controlled due to many reasons. The widespread uses of antibiotics, together with the length of time over which they have been available have led to major problems of resistant organisms contributing to morbidity and mortality. This study was aimed to assess bacterial isolates and their drug susceptibility patterns from patients with pus and/or wound discharge.A retrospective study was conducted at Gondar University Hospital from all individuals who provide pus and/or wound discharge sample from September, 2009 to August, 2012. Socio-demographic and laboratory results were collected from the University Hospital Microbiology Laboratory unit registration books by using a standard data collection format. Data were analyzed using SPSS version 20 software. P-value ≤ 0.05 was considered statistically significant.A total of 628 study subjects were included in the study with bacterial isolation rate of 441 (70.2%). Of all, 344 (54.8%) were males. Two hundred eighty two (63.9%) of the isolates were gram positive and 159 (36.1%) were gram negative. About 331/ 441 (75.0%) of the total isolates were Staphylococcus aureus (32.9%), Coagulase Negative staphylococci (14.7%), Streptococcus spp. (11.6%), Escherichia coli (9.5%), Klebsiella spp. (6.3%). The result showed that 66.2% of the isolates were resistant to tetracycline, followed 59.8% for ampicillin, 59.1% for cotrimoxazole, 51.7% for penicillin; least resistant being 6.3% for gentamycin.High prevalence of bacterial isolates were found; S. aureus being the dominant. Most of the isolates were resistant to many of the antibiotics tested where all isolates of Pseudomonas spp. being resistant to two or more antibiotics. Antibiotic susceptibility test is necessary for effective control of wound infections.